GKI GCC; Magang; Aspek Musikal; Aspek Non musikal - Hendrik Leonard Simanjuntak; Sella Noviyanti Saragih; Karunia Debora Claudia; Domilika Panggabean; Kartini R. M. Manalu (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
Internship is a media specifically provided by the Music of Arts Department University of HKBP Nommensen to facilitate students to have the opportunity to study outside the campus for one semester. One form of internship offered is student participation in music ministry in the church. There are two main aspects that students prepare before the internship is carried out, namely; musical and non-musical aspects. The final result of the internship is connection, collaboration, cooperation, and scientific implications. The implementation of the internship received a positive response from church leaders, congregations, music teams, multimedia teams, and sunday school teachers.